Bishop John Vitez and Early Renaissance Central Europe : The Humanist Kingmaker. - Matić, Tomislav. (Beyond Medieval Europe Series, 2022)
The first biography of John Vitez, an influential figure of the Early Renaissance, presenting a complex picture of cultural, political, and religious developments in Central Europe.